Envisioning Post-pandemic Digital Neurological, Psychiatric and Mental Health Care - Khanna, Amit; Jones, Graham B. (Frontiers in Digital Health, 2021)
The SARS-Cov-2 pandemic placed a dramatic burden on managed healthcare and perhaps nowhere as evident as in neurological and psychiatric disease care. This said, the duration of the pandemic mandated adaptability of the entire care system and the oft-vaunted benefits of telehealth and telemedicine were subjected to deep scrutiny at scale. Positive experiences were reported by both patients and providers from routine check-ups, to use of cognitive behavioral therapy associated with mental disorders, and management of complex diseases such as multiple sclerosis and other neurological and psychiatric conditions. Integration into standard care looks likely in the post pandemic era with many healthcare systems moving to expand reimbursement categories and develop equitable incentive models for developers and providers. In this commentary we share perspective on how the future of care may evolve through hybrid delivery models, and the advent of new therapeutic approaches which can address pain points identified during the pandemic.